Tratamento multiprofissional da obesidade em mulheres - Bevilaqua, Cheila Aparecida (2012)
Currently regarded as an epidemic, obesity has grown in alarming rate in developed and developing countries alike, causing extensive harm to society.Nevertheless, a wide variety of treatments are available, including dieting, regular exercise, behavioral changes, pharmacological treatment and even surgical intervention. However, researchers point out that the best way to control this disease is by adopting new behaviors. The objective of this study was to evaluate the effect of a multi-professional treatment program for obesity in women. It was an intervention study that consisted of practicing physical exercise three timesa week, nutritional guidance and health education once a week, for 16 weeks. A total of 33 women took part in the study, 13 in the intervention group (IG) and 20 in the control group (CG). The study evaluated anthropometrics variables, body composition, clinical and biochemical parameters, as well an evaluation of the stage of readiness for behavioral change and health-related fitness. The results indicated significant improvements by IG women for anthropometric (weight, BMI, AC and WHR), body composition (fat mass and percentage) and biochemical variables (total cholesterol and glycemia). For the stage of readiness for behavioral change, it was detected that IG women showed better change indicators than women in CG. Significant improvements could also be observed in the physical fitness tests (flexibility, abdominal strength and VO2máx) among women who took part in the program. It can thus be concluded that the interventions were efficient in treating obesity made a contribution to the overall improvement in the health of the participants.